PERTANGGUNGJAWABAN HUKUM PENYELUNDUPAN MANUSIA DALAM TINDAK PIDANA KEIMIGRASIAN (STUDI TERHADAP PUTUSAN NOMOR 817/PID.SUS/2021/PN.BLS) - Abdus Salam Rezeky; Rusdi Rusdi; Widya Manurung; Tika Juwanti; Sofyan Panjaitan; Erwin Syahputra; Ramadhan Siagian; Fitri Anggraini; Agung Wirahadi Prabowo; Sri Kumala Devi; Fiqria Muzdalifah; Syafrillah Hamdani; Muhammad Ardiansyah; Syafira Hasrill; Ari Ayusri; Muhammad Dzulkhairil; Andreansyah Sitorus; Endi Hardandi; Bobi Rahmawan; Rudi Gunawan; Tri Vena Agintha Barus; Lintang Alfafaruq (Nusantara Hasana Berdikari, 2022)
The purpose of this study was to determine the legal considerations of the Panel of Judges in imposing criminal penalties on the perpetrators of immigration crimes and their sentencing. The method used is a normative legal research method. The judge's judgment is correct because the judge in making a decision pays attention to juridical and non-juridical considerations. The defendant is subject to sanctions as stipulated in Article 120 paragraph (2) of the Republic of Indonesia Law Number 6 of 2011 concerning Immigration and Law Number 8 of 1981 concerning the Criminal Procedure Code and other relevant laws and regulations. The government must tighten supervision and monitoring of coastal areas that are vulnerable to entry and exit of Indonesian territory and require firmness for law enforcement officers in punishing perpetrators of immigration crimes because this can harm and have an impact on the security of the Unitary State of the Republic of Indonesia.